A panel data analysis of trade creation and trade diversion effects: The case of ASEAN-China Free Trade Area (ACFTA) - Shanping Yang; Inmaculada Martínez-Zarzoso (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2013)
This study uses a theoretically justified gravity model of trade to examine the impact of the ASEAN-China Free Trade Agreement (ACFTA) on exports, focusing on trade creation and diversion effects. The model is tested on a sample of 31 countries over the period dating from 1995 to 2010 using aggregate and disaggregated export data for agricultural raw materials, manufactured goods and chemical products, as well as machinery and transport equipment. In order to obtain unbiased estimates, multilateral resistance terms are included as regressors and the endogeneity bias of the FTA variables is addressed by controlling for the unobserved specific heterogeneity that is specific to each trade flow. The results indicate that ACFTA leads to substantial and significant trade creation. Using disaggregated data, the significant and positive relationship between exports and ACFTA can be confirmed in the case of both manufactured goods and also chemical products.
Keywords: F14; F15; 330; gravity model; panel data; trade creation and trade diversion effects; ACFTA